The impact of energy demand on economic growth: A new empirical evidence for Madagascar - Ramaharo, Franck; Razanajatovo, Yves, Heritiana, Mihaja; Ravelomanantsoa, Fabienne, Mahefatiana; Ramarosandratana, Saotra, Finiavana, Melodia; Aljaona, Miora, Emanuella (My University, 2024)
This study investigates the impact of energy demand on Madagascar's economic growth from 2007Q1 to 2022Q4. Drawing upon a rich dataset from Malagasy sources, we applied the ARDL bounds testing approach and found cointegration among the series. We found that, in the long run, electricity and petroleum consumption have positive significant effects on economic growth, while energy imports and global prices have negative significant effects. We further applied Granger-causality test based on Error Correction Model to examine causal relationships. The results revealed that in the short run, there are unidirectional causal effects running from electricity consumption, energy imports, and global prices to economic growth. The test also revealed that both energy demand and global prices have a long-run causal effect on economic growth. Our findings confirms that Madagascar is an energy-dependent economy, and provide valuable insights for policymakers to design effective energy policies that promote economic growth and energy security.
Keywords: economic growth; electricity consumption; energy demand; energy imports; Madagascar; petroleum consumption